2023
DOI: 10.1021/acs.jpclett.3c02061
|View full text |Cite
|
Sign up to set email alerts
|

Surface Engineering of Methylammonium Lead Bromide Perovskite Crystals for Enhanced X-ray Detection

Abraha Tadese Gidey,
Yuki Haruta,
Artur P. Herman
et al.

Abstract: The surface quality of lead halide perovskite crystals can extremely influence their optoelectronic properties and device performance. Here, we report a surface engineering crystallization technique in which we in situ grow a polycrystalline methylammonium lead tribromide (MAPbBr3) film on top of bulk mm-sized single crystals. Such MAPbBr3 crystals with a MAPbBr3 passivating film display intense green emission under UV light. X-ray photoelectron spectroscopy demonstrates that these crystals with emissive surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…The contribution of the air ionization in the perovskite X-ray detector was also investigated with a detector reported in our previous work (Au/MAPbBr 3 /Ga, vertical structure) . As shown in Figure S14, the response current to X-rays with a dose rate of 29.4 μGy s –1 at the applied bias of 5 V has decreased from 0.83 nA to 0.69 nA under a vacuum compared to the ambient air.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…The contribution of the air ionization in the perovskite X-ray detector was also investigated with a detector reported in our previous work (Au/MAPbBr 3 /Ga, vertical structure) . As shown in Figure S14, the response current to X-rays with a dose rate of 29.4 μGy s –1 at the applied bias of 5 V has decreased from 0.83 nA to 0.69 nA under a vacuum compared to the ambient air.…”
mentioning
confidence: 85%
“…The contribution of the air ionization in the perovskite X-ray detector was also investigated with a detector reported in our previous work (Au/MAPbBr 3 /Ga, vertical structure). 34 As shown in Figure S14, the response current to X-rays with a dose rate of 29.4 μGy s −1 at the applied bias of 5 V has decreased from 0.83 nA to 0.69 nA under a vacuum compared to the ambient air. The difference of 0.14 nA is too large to attribute this entirely to the air ionization current, and the possibility remains that the performance of the detector itself changed in vacuum and in air.…”
mentioning
confidence: 93%
“…Therefore, we can reduce the defect density and improve the film coverage by changing ligands and passivating surface defects, so as to improve exciton radiative recombination, PLQY, and EQE. [ 115–119 ] The balance factor of charge injection can also be improved by changing the barrier between the transport layer and the light‐emitting layer and the EQE can be improved. By adding patterned grating, EQE is added by light extraction technology.…”
Section: The Fundamentals Of Gpeledsmentioning
confidence: 99%
“…Boopathi et al 22 developed a crystallization technique involving solvent acidolysis crystallization (SAC) that relied on the acidolysis of N -methylformamide (NMF) for in situ formation of the MA cation to grow MAPbBr 3 perovskite SCs showing green edge emission under UV light. Gidey et al 23 reported in situ growth of a polycrystalline MAPbBr 3 layer on the top surface of bulk millimeter-sized SCs by modifying the precursor solution concentration along with using dichloromethane, an antisolvent of dimethylformamide, to initiate the crystallization, and they obtained 5-fold improved sensitivity of X-ray detection. In our previous report, we optimized the concentration of antisolvent tetrahydrofuran (THF) to grow bigger-sized (≥5 mm) and high-quality MAPbBr 3 perovskite SCs displaying bright emission from the entire top and side surface under UV light.…”
mentioning
confidence: 99%